2012
DOI: 10.1186/1865-1380-5-40
|View full text |Cite
|
Sign up to set email alerts
|

Major incident preparedness and on-site work among Norwegian rescue personnel – a cross-sectional study

Abstract: BackgroundA major incident has occurred when the number of live casualties, severity, type of incident or location requires extraordinary resources. Major incident management is interdisciplinary and involves triage, treatment and transport of patients. We aimed to investigate experiences within major incident preparedness and management among Norwegian rescue workers.MethodsA questionnaire was answered by 918 rescue workers across Norway. Questions rated from 1 (doesn’t work) to 7 (works excellently) are pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…This may reflect the significant relationship between preparedness and a higher degree of role clarity during the terror events, and thereby highlight the importance of regular systematic training. This is in accordance with studies of systematic team-based training in trauma care that showed beneficial in-hospital effects [ 4 ], well-functioning cooperation [ 22 ] and increasing role clarity after systematic multidisciplinary team training [ 23 ].…”
Section: Discussionsupporting
confidence: 90%
“…This may reflect the significant relationship between preparedness and a higher degree of role clarity during the terror events, and thereby highlight the importance of regular systematic training. This is in accordance with studies of systematic team-based training in trauma care that showed beneficial in-hospital effects [ 4 ], well-functioning cooperation [ 22 ] and increasing role clarity after systematic multidisciplinary team training [ 23 ].…”
Section: Discussionsupporting
confidence: 90%
“…Patients thus become a “boundary object,” where cross‐boundary work is actualized (Lindberg & Czarniawska, ). Emergency response learning in Norway was studied by Pollestad and Steinnes (), Fattah, Krüger, Andersen, Vigerust, and Rehn (), and Sommer ().…”
Section: Introductionmentioning
confidence: 99%
“…Hydraulic tools and chains are also needed. RE was introduced in the Interdisciplinary Emergency Service Cooperation (TAS) courses in 2002 [ 5 , 6 ]. Some 16500 participants from fire departments, police and EMS in Norway have participated in the more than 450 TAS courses held so far.…”
Section: Introductionmentioning
confidence: 99%